Effect of Kalavasti and Nasya with Karpasathyadi Taila in the Management of Pakshaghata W. S. R to Hemiplegia – A Comparative Clinical Study - Gupta , Anil (International Research Journal of Ayurveda & Yoga, 2024)
Recentrapid socioeconomic changes have led to a concomitant change in people’s lifestyle, leading to work-related stress and altered food habits, raising the risk of hypertension. Those factors, coupled with an increase in the average life expectancy, are expected to have an impact on the occurrence of stroke disorderin India. In India, these data are more horrible as 64,000 death